Agriculture Output Growth in East Java: An Input-Output Analysis Beetwen 1985-1990 and 1994-2000 - Ratya Anindita; Agustina Shinta (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2010)
-